Effect of Frozen Storage on Physical and Chemical Quality Changes in White Leg Litopenaeus vannamei, Beheaded at Various Stages of Rigor - Bhat, Tariq Hussain; Mithilesh Kumar Chouksey; Amjad Khansaheb Balange; Binaya Bhusan Nayak (Fishery Technology, 2022)
In this study effect of severing skeletal muscle by beheading at different stages of rigor on the quality of pacific white shrimp Litopenaeus vannamei during frozen storage for a period of six months was investigated by physical, chemical and sensory evaluation. Moisture content, NPN and Sarcoplasmic protein showed a decreasing trend, whereastotalprotein content increased in all the treatments during frozen storage. pH value showed anincreasing Â trend during the storage study in all the treatments. Â TMA-N, TVB-N, Peroxide value and Thiobarbituric acid value also increased Â in all the treatments during the storage study, however all the values were well within the acceptable limit.There was a significant decrease in the hardness, cohesiveness, springiness and chewiness in all the treatments during the storage. The final lower value of hardness was recorded in T3 indicating that serving of skeletal muscle in pre-rigor stage resulted in the better textural properties. The initial highest L* value was found in T2 followed by T1 and T3. Values of a* and b* showed a decreasing trends during the storage study indicating greener and blue colouration. Colour parameters showed significant differences (p<0.05) as storage progressed. Sensory score showed a decreasing trend with the storage reaching to the final value of as low as 6.38. However the shrimp were still acceptable after six months of frozen storage. There was not a significant difference among different treatments indicating that severing of skeletal muscle in different stages of rigor does not affect the quality of the shrimp.